2019
DOI: 10.1557/jmr.2019.33
|View full text |Cite
|
Sign up to set email alerts
|

Review of surface water interactions with metal oxide nanoparticles

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…The data for the loosely bound water in natrolite is quite similar in form to the heat capacity of the outer layers of water on titania nanoparticles (Calvin et al, 2019), which do not exhibit This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America. The published version is subject to change.…”
Section: Heat Capacity Of Zeolitic Watermentioning
confidence: 78%
“…The data for the loosely bound water in natrolite is quite similar in form to the heat capacity of the outer layers of water on titania nanoparticles (Calvin et al, 2019), which do not exhibit This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America. The published version is subject to change.…”
Section: Heat Capacity Of Zeolitic Watermentioning
confidence: 78%
“…The interaction between MgO particles and water is manifold and leads to different structures depending on the concentration of water and its form of admission to the precleaned particle surfaces (i.e., contact with water vapor or immersion into a condensed bulk liquid). At partial pressures in the 1–30 mbar range, which is comparable to those in air, water adsorption leads to coverages of a few layers, 5 , 43 and the dissociative adsorption of water results in surface energy changes that can trigger the formation of MgO nanocube stacking. Indeed, water vapor exposure of a MgO nanocube powder sample that was previously outgassed at T = 1173 K and at p < 10 –5 mbar ( Figure 2 a) has a profound impact on the microstructure of the powder.…”
Section: Resultsmentioning
confidence: 99%
“…Modeling of water adsorption on forsterite surface suggests that the adsorption on the (110) surface leads to water dissociation, , while the (010) surface favors molecular water. ,, Therefore, on average, the surface of each forsterite nanoparticle is partially hydroxylated or hydrated depending on the sum of the contributions from multiple surfaces. The inherent water layers on TiO 2 nanoparticles have been studied due to their hygroscopic nature. , These indicate the existence of a hydroxylation/hydration layer that stabilizes the nanoparticles and can only be removed at a threshold temperature coincident with grain growth/coarsening, , e.g., ∼600 °C for anatase TiO 2 nanoparticles ranging from 7.7 to 32 nm . Similarly, a water desorption experiment using polished olivine single crystals indicated that the major surface species, i.e., hydroxyl groups, can be stable on the surface up to 900 K (627 °C) .…”
Section: Materials and Experimentsmentioning
confidence: 99%